Bleeding outcomes and musculoskeletal function in adolescents having severe hemophilia A: a case series - Primacakti, Fitri; Prasetyo, Marcel; Fauzia, Sri Novia; Sarita, Raisa Cecilia; Chozie, Novie Amelia (Paediatrica Indonesiana, 2025)
As an emerging country, Indonesia is still in the process of implementing prophylaxis as a standard of care for managing hemophilia with limited real-world evidence in Indonesian patients. This case series details the effects of tertiary prophylaxis with an intermediate dose of factor VIII concentrate on bleeding outcomes and musculoskeletal function in three Indonesian adolescents suffering from severe haemophilia A and associated arthropathy.